Central proliferative diabetic retinopathy: evaluation and management - Mohamed I Elkasaby; Hazem Mohamed Azab; Maged Adly Naguib; Ali Hendy El Ghamdi; Mostafa Mahmoud Darwish (Wolters Kluwer Medknow Publications, 2017)
Aims The aim of this study was to evaluate the outcome of central proliferative diabetic retinopathy (PDR) after pars planavitrectomy. Patients and methods This prospective, observation, randomized study included 90 eyes of 64 patients with central PDR who underwent pars planavitrectomy by a single vitreoretinal surgeon. Patients were followed up on the second postoperative day, at 1 week, 2 weeks, and at 1, 3, 6, and 12 months after surgery. Clinical outcomes were recorded at every visit. Results Ninety eyes of 64 patients with severe PDR that involved the macula and central retina were studied. Of 36 patients 16 (44.4%) patients were female, whereas 20 (55.5%) patients out of 36 were male. Their ages ranged from 20 to 70 years. Out of 36 patients 12 (33.3%)had bilateral PDR. 20 of 36 (55.5%) patients had type І diabetes mellitus and 16 (44.4%) of 36 patients had type ІІ.